The Openflexure Project. The Technical Challenges Of Co-Developing A Microscope In The Uk And Tanzania - Stirling, Julian; Sanga, Valerian Linus; Nyakyi, Paul; Mwakajinga, Grace; Collins, Joel; Bumke, Kaspar; Knapper, Joe; Meng, Qingxin; McDermott, Samuel; Bowman, Richard (My University, 2020)
The OpenFlexure Microscope is a 3D-printed laboratory-grade motorized microscope. Over the past 3 years, the microscope has primarily been co-developed between the University of Bath and the Tanzanian engineering company STICLab. We are beginning the process of preparing the microscope for medical certification, as an in-vitro diagnostic device. In this paper we detail the technical challenges of remote design of a complex scientific instrument. We believe that identifying and solving these issues is essential if we are to encourage research organizations in the Global North to design instrumentation with Africans, rather than "for Africa".
Keywords: Microscopy; Co-Design; Medical Devices